2011
DOI: 10.1039/c0cc01742f
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced selectivity in acetylenehydrogenation by ligand modified Pd/TiO2catalysts

Abstract: Modification of Pd/TiO(2) catalyst by adsorption of triphenylphosphine and phenyl sulfide leads to markedly enhanced selectivity for acetylene hydrogenation in the presence of ethylene and excess hydrogen. Similar selectivities were maintained in cases where ligand decomposition took place and sulfur was retained on the catalyst surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 16 publications
2
61
2
Order By: Relevance
“…The group of Anderson investigated the adsorption of organic sulfur [46][47][48][49] and phosphorous [48][49][50] modifiers on acetylene hydrogenation. Diphenylsulfide and triphenylphosphine were adsorbed onto a Pd/TiO 2 catalyst by impregnation from a hexane solution.…”
Section: Organic Selectivity Modifiersmentioning
confidence: 99%
“…The group of Anderson investigated the adsorption of organic sulfur [46][47][48][49] and phosphorous [48][49][50] modifiers on acetylene hydrogenation. Diphenylsulfide and triphenylphosphine were adsorbed onto a Pd/TiO 2 catalyst by impregnation from a hexane solution.…”
Section: Organic Selectivity Modifiersmentioning
confidence: 99%
“…The industrial process typically takes place at low temperature (313-393 K) over a PdAg 'skin' or egg-shell catalyst [25] where Pd is the active metal. The role of Ag is to dilute Pd ensemble size [23] and limit palladium hydride formation [26] which has been shown to be detrimental for achieving high alkene selectivity [27][28][29][30][31][32], although a similar effect may be achieved by using organic sulfur [33][34][35][36] and phosphorous modifiers [33,37]. Several other monometallic [38][39][40], bimetallic [41][42][43][44], trimetallic [45] and metal-free catalysts [46,47] have been shown to offer high alkene selectivity, although they typically require activation and/or use at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sajiki's group [14][15][16] produced a series of organic sulfide modified Pd/C catalysts, which moderately depressed the catalyst activity of Pd/C to acquire distinguishing chemoselectivity on hydrogenation. Several studies have revealed that different organic sulfides were able to enhance the selectivity of supported noble metal catalysts in the hydrogenation reactions [7][8][9][15][16][17][18]. However, there is still little information about the effect of organic sulfides on the structure, the adsorption feature and the properties of noble metal catalysts.…”
Section: Introductionmentioning
confidence: 98%
“…In order to improve the selectivity of the supported noble metal catalysts, many studies have been carried out. The use of carbon monoxide and sulfides as poisons for noble metal catalysts has been recognized as a reasonable method to enhance the selectivity of the catalysts [5][6][7][8][9][10][11][12][13][14][15][16][17]. Supported palladium catalysts modified by CO showed a good performance on the selective removal of acetylene from ethylene rich feeds [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation